IMPACT OF SUBSTITUTING THE OF EXPORTED AGRICULTURAL PRODUCTS FOR DOMESTIC PROCESSING ON BRAZILIAN ECONOMY - Alberto Gonçalves Jr, Carlos Alberto; de Camargo, Carla Cristiane; Staduto, Jefferson A. Ramundo; Lopes, Ricardo Luis (Revista Brasileira de Gestão e Desenvolvimento Regional, 2023)
This study examined the potential economic growth caused by substituting the export of the agrifood fresh products industry for domestic processing. We used an interregional input-output system measured for 2013. Results showed that this substitution led to a R$ 4.86 billion increase in the national GPV. Moreover, given the industrial concentration in the Southeast region of the country, this substitution can contribute to increased economic inequality among the Federation Units. This theoretical exercise, besides contributing to the literature on the importance of adding value to production by processing agricultural commodities, may help guide policies aimed at promoting economic growth.